“Safety Fatigue”: Symptoms, Causes, Solutions - M. Kessler, John (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2022)
I have had the pleasure of many visits to Brazil since 2001. During these visits, I have collaborated with ANVISA on training programs at the start of the Sentinel Hospital program. I have lectured on medication safety topics to students, practitioners, private companies, and healthcare administrators. I have worked closely with safety organizations such as ISMP- Brazil, a national leader in promoting safety awareness and safe practices. I have seen Brazil experience an awakening to the problems of safety in healthcare. Over these last 16 years, good things have happened because of the personal dedication of professionals, leaders, and organizations devoted to safety. There have been well-attended local, regional and national congresses on safety. In general, there is an appetite for learning how to be safer and how to make changes that improve quality.